Designing an Application for Direct Cash Assistance Allocation Using Laravel at Sepang District Office - Sunardi, Sunardi; Auliana, Sigit; Pratama, Gelard Untirtha; Permana, Basuki; Nugraha, Asep Darma (ARRUS Journal of Engineering and Technology, 2024)
This research aims to design an information system for receiving direct cash assistance funds at the Sepang sub-district office, the sub-district can use this system to make it easier to receive direct cash assistance funds. Researchers use the PHP programming language, assisted by the Laravel Framework, and use MYSQL as a database. For the software development stage, use the saw method. Data collection techniques in research use observation, interviews and literature studies. The results of this research are an application for determining the receipt of direct cash assistance funds in the Sepang sub-district which is expected to make it easier for the sub-district to implement the receipt of direct cash assistance funds.